Relationship between self concepts and personality and students’ academic performance in selected secondary schools - Yahaya, Azizi; Ramli, Jamaluddin; Boon, Yusof; Abd. Ghaffar, Mohd. Najib; Zakariya, Zurihanmi (EurojournalPublication, 2009)
The purpose of this research is to determine the relationship between the self-concept and personality of students with academic achievement. The sample consists of 270 students from six secondary schools were chosen by using stratified randomly method in Kluang, Johor. The pilot study was done in order to determine the reliability and suitability of the questionnaires. Meanwhile Cronbach Alpha was used to determine the internal consistency of the questionnaires. The reliability value of Cronbach Alpha for the whole set of questionnaires used was 0.8432. The questionnaire for self-concept was modified from Tennessee Self-concept Scale that was created by Fitts (1971). Meanwhile the questionnaire for personality was modified from the Junior Eysenck Personality Inventory (JEPI) that was created by H. J. Eysenck (1967). The descriptive statistics such as frequency, percentages, mean and standard deviation were used to analyze the dominant dimension in student’s self-concept. Other than that, inferential statistic such as t-test was used to analyze the difference between the self-concept and personality of students according to gender. Meanwhile, Pearson correlations were used at significant level 0.05 to analyze the relationship between self-concept and personality of students with their academic achievement. The research finding showed that the dominant dimension of selfconcept was family self-concept. Beside that, t-test analysis showed that there was no significance difference between dimension of self-concept and personality of students according to gender. Pearson correlations analysis showed that there were no significance relation between dimension of self-concept and personality with student’s academic achievement. Therefore, suggestions were made to increase the student’s self-concept and the tendency of their positive personality in order to enhance their academic achievement.